Genetic and molecular studies of rare variation in schizophrenia - Fahey, Ciara (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2014)
Schizophrenia (SCZ) is a severe and debilitating disorder and it has a worldwide prevalence estimated at approximately 1%. The underlying pathogenesis of SCZ is poorly understood and there is a great need for diagnostic tools and new therapeutic interventions. It has a very strong genetic component but its genetic architecture remains to be elucidated.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin